Calcium Carbonate Removal Via Direct Contact Membrane Distillation - Asrafa, Mohamad Fikri (Universiti Sains Malaysia, 2018)
This research studied in the performance of direct contact membrane distillation in removing calcium carbonate solution or water softening. The important parameter investigated include feed concentration, feed temperature and feed flowrate. The feed concentration are vary from 0.1g/L CaCO3 to 9.0g/L CaCO3. The result indicated that permeate flux decrease as the feed concentration increase. The higher feed concentration lead to deposition of solute on the membrane surface and cause fouling, thus the permeate flux decrease. The feed temperature and feed flowrate are vary from 60°C to 80°C and 18.92L/hr to 27.85L/hr respectively. The permeate flux increase linearly with increase in feed temperature and feed flowrate. DCMD is a thermal driven process, increase in feed temperature will increase the driving force for the water vapour pass through the membrane. Increase in feed flowrate will decrease the temperature boundary layer and enhance the separation process. The fouling phenomena was observed when the 9.0g/L CaCO3 run for 8 hour. Permeate flux start to decline after 6 hours of DCMD process. The observed deposition of the solute on the membrane surface prove that fouling phenomena did occur via cake deposition before wetting and pore blocking after wetting taken placed.